Onboard power line conditioning system for an electric or hybrid vehicle - KAJOUKE LATEEF A; PERISIC MILUN (2013)
The invention relates to an onboard power line conditioning system for an electric or hybrid vehicle. A power line quality conditioning system for a vehicle includes an onboard rechargeable direct current (DC) energy storage system and an onboard electrical system coupled to the energy storage system. The energy storage system provides DC energy to drive an electric traction motor of the vehicle. The electrical system operates in a charging mode such that alternating current (AC) energy from a power grid external to the vehicle is converted to DC energy to charge the DC energy storage system. The electrical system also operates in a vehicle-to-grid power conditioning mode such that DC energy from the DC energy storage system is converted to AC energy to condition an AC voltage of the power grid.